Sortir du cadre franquiste : quelques figures intellectuelles de la « rupture négociée » pour El País et la presse de la transition - Chantal Chartier (Cahiers de Civilisation Espagnole Contemporaine)
The present study focuses upon the role of the print media in continuing the cultural liberal tradition during the Transition to democracy, after the Ilustración (Enlightenment), Regeneracionismo and the ILE (Institución Libre de Enseñanza). The print media claims tutelary figures such as Unamuno and Ortega y Gasset and seeks to situate itself within a current of liberal thought that has resisted the censorship imposed by Franco. By referring to recognized Spanish intellectuals, or laying particular emphasis on the resistance of ex-Phalangist intellectuals or the successors of the liberal Ortega, the affirmation of this continuity finally unites all sides of the political and ideological spectrum in the name of a great national reconciliation (Marañón, Laín Entralgo, Ridruejo, Eugenio D’Ors, Madariaga, Aranguren, Julián Marías, Machado, Alberti). The figure of the intellectual changes and Aranguren uses the Gramscian concept of the collective intellectual for the benefit of the newspaper El País.